Quality Profile of Riparian Zone and Vegetation Quality in Amprong River, Tumpang District Based on QBR index and NDVI - Hamdani Dwi Prasetyo; Majida Ramadhan (University of Brawijaya, 2021)
Riparian zones provide ecosystem services depending on the quality of riparian vegetation and vegetation health. The role of riparian vegetation was determined by the total cover, cover structure, vegetation cover quality, and channel alteration of the riparian zone. Vegetation health was to determine the condition of the riparian zone of the Amprong river. In determining the quality of the riparian zone and the quality of the vegetation, it is done by observing the riparian zone of the Amprong river. The results of field observations were analyzed using the QBR index. Vegetation quality was also observed using the Normalized Difference Vegetation Index. The quality profile of the Amprong river riparian zone is in the medium category, while stations 4.2 and 4.3 are in a good category. The good category is obtained from the high total cover dam cover structure value. Meanwhile, the low QBR value is caused by the value of disturbance in the riparian zone in the form of agricultural activities, community settlements, garbage, land conversion to permanent buildings in the riparian zone. The size of the tree canopy at several stations has an impact on the QBR index value. Vegetation connectivity to rivers also helps in maintaining the quality of the riparian zone. Vegetation health on a scale of 0.012 to 0.371 indicates that the sampling site is in good condition. However, this condition will worsen if there is pressure from human activities. Sustainable management is needed by improving the quality of vegetation and reducing disturbance to the riparian zone.